On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India - Chan, Tin-Yam; Chakraborty, Rekha Devi; Purushothaman, P.; Kuberan, G.; Yang, Chien-Hui (Zootaxa, 2018)
The availability of Indian specimens of Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 provided more information on the taxonomy around these two species. Moreover, it is the first record of P. persica to India. Although P. taiwanica Chan and Yu, 2000 is superficially rather similar to P. persica, there are many differences between them and probably it is inappropriate to establish a species group for these two species. It is likely that all previous records of P. ensis (A. Milne-Edwards, 1881) from India actually represent P. reflexa Chace, 1985. Nevertheless, the present Indian specimens of P. reflexa have more than 10% COI sequence divergence from the topotypic materials of both P. ensis and P. reflexa, and the epipods at the pereiopods III and IV reduced or absent. This data further highlights the confusing taxonomy in the “P. ensis” group.